THE WITCH'S LOST CAT - Blyton, Enid; Paterson, Alex (London : Egmont UK Limited, 2019)
Never in their wildest dreams, could Mollie and Peter have imagined something so wonderful as a magic Wishing-Chair that will fly you anywhere and grant your every wish! And so when their little black cat, Whiskers, goes missing, they know just who to call upon to help them find her!
Keywords: Imagination -- Juvenile fiction; Cats. -- Juvenile fiction; Magic. -- Juvenile fiction